Innovative Approaches to Surgical Treatment of Hypospadias in Children - o’g’li, Shukrulloyev Fayozjon Zokirjon (American Journal of Bioscience and Clinical Integrity, 2024)
In the literature, greater attention has traditionally been paid to urethroplasty techniques. Consequently, issues such as the correction of penile curvature have long been discussed only within the context of the question: "Which is better: methods with or without preservation of the urethral plate?" Essentially, this debate boils down to the question: "Does a chordee exist?". Thus, the method proposed by R. Nesbit back in 1965 for correcting penile curvature, along with its modification by L. Baskin, remains the most popular to date.